Pengembangan LKPD Berbantuan Aplikasi Canva Berbasis Etnomatematika untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa - Wahyuni, Sri; Ilmi, Nurul Khautsar; Sari, Dira Puspita (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This development research aims to find out; (a) Validity of LKPD assisted by the Canva application on circle material based on ethnomathematics to improve students' mathematical communication skills, (b) Practicality of LKPD assisted by the Canva application on circle material based on ethnomathematics to improve students' mathematical communication skills and (c) Effectiveness of LKPD assisted by the Canva application on material Ethnomathematics-Based Circles to Improve Students' Mathematical Communication Skills. The type of research used is Research and Development (RnD). The research model used is the 4D Model (Define, Design, Development and Disseminate). The subjects in this research were 30 class VIII students at MTs Muhammadiyah Sidomulyo. The results of this research analysis are; (a) The LKPD developed meets the valid category and the percentage value obtained is 94.25% with the criteria "Very Appropriate" (b) The LKPD developed meets the practical category and the percentage value obtained is 93.33% with the criteria "Very Good" (3) The LKPD that was developed met the effective category with a complete learning result obtained by a percentage of 86.66% and students who completed the minimum KKM score, namely 27 students with classical completeness obtained a percentage of 90%. This shows that overall, the development of LKPD assisted by the Canva application on ethnomathematics-based circle material to improve the mathematical communication skills of class VIII students at MTs Muhammadiyah Sidomulyo is included in the valid, practical and effective category.